2021
DOI: 10.3390/rs14010003
|View full text |Cite
|
Sign up to set email alerts
|

Developing Multi-Source Indices to Discriminate between Native Tropical Forests, Oil Palm and Rubber Plantations in Indonesia

Abstract: Over the last 18 years, Indonesia has experienced significant deforestation due to the expansion of oil palm and rubber plantations. Accurate land cover maps are essential for policymakers to track and manage land change to support sustainable forest management and investment decisions. An automatic digital processing (ADP) method is currently used to develop land cover change maps for Indonesia, based on optical imaging (Landsat). Such maps produce only forest and non-forest classes, and often oil palm and ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The average NDMI value was identified as 0.55 for Landsat-7 ETM+ image and 0.80 for Landsat-8 OLI image. These results indicated that the vegetation was healthy and had a dense canopy cover [73,90]. However, non-mangrove pixels remained, particularly in the terrestrial vegetation region, but were still grouped into the mangrove class.…”
Section: Distribution Of Mangrove Forests In 2002mentioning
confidence: 90%
See 1 more Smart Citation
“…The average NDMI value was identified as 0.55 for Landsat-7 ETM+ image and 0.80 for Landsat-8 OLI image. These results indicated that the vegetation was healthy and had a dense canopy cover [73,90]. However, non-mangrove pixels remained, particularly in the terrestrial vegetation region, but were still grouped into the mangrove class.…”
Section: Distribution Of Mangrove Forests In 2002mentioning
confidence: 90%
“…Decision trees have been widely used for land cover classification, particularly with remote sensing technology approaches [70], and are often used to integrate multi-source data, such as optical imagery and SAR [71][72][73]. Several previous studies have also developed a DT algorithm to identify the presence of mangrove forests [21,26].…”
Section: Decision Tree Algorithmmentioning
confidence: 99%
“…Spectral-temporal data were extracted from the reference dataset at these points, and three specific indices were applied to analyze and interpret the data. These indices (VH/VV ratio, NDVI, NDMI) are widely used in the literature to define phenological stages and biophysical parameters of vegetation [17,86,87]. The VH/VV ratio in decibels is given by: VH/VV ratio (dB) = VH (dB) − VV (dB)…”
Section: Hazelnut Groves Characterizationmentioning
confidence: 99%
“…It was observed that there is misclassification of natural forests and human raised plantations like oil palm, and rubber in Ghana and Indonesia as cited by Jacob Abramowitz et al [10] and Inggit et al [11], respectively. In Bangladesh, a standard classification system was introduced to provide consistent Land cover information [12].…”
Section: Introductionmentioning
confidence: 99%